2012
DOI: 10.1002/jrs.3144
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Raman spectroscopy and spectroelectrochemistry characterization of carbon nanotubes/polyaniline thin film obtained through interfacial polymerization

Abstract: Thin, transparent, and self‐assembled films of neat polyaniline and polyaniline/carbon nanotube nanocomposites were deposited over glass substrates by interfacial polymerization. The effect of the carbon nanotubes on the structure and conformation of the polyaniline, and the type of interaction between the polymer and the nanotubes, have been studied by resonant Raman spectroscopy and UV–Vis and Raman spectroelectrochemistry. The results indicate clearly that the carbon nanotubes induce important changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 45 publications
(55 reference statements)
3
53
0
1
Order By: Relevance
“…First, the Raman spectrum of PANI bulk was analysed to serve as a reference, Figure 4a). The analysis of main regions of PANI-ES and their assignments are supported by data from other works [31][32][33][34]. .…”
Section: Raman Spectroscopysupporting
confidence: 77%
“…First, the Raman spectrum of PANI bulk was analysed to serve as a reference, Figure 4a). The analysis of main regions of PANI-ES and their assignments are supported by data from other works [31][32][33][34]. .…”
Section: Raman Spectroscopysupporting
confidence: 77%
“…[ 22 , 28 ] The presence of carbon nanotubes in these green fi lms (typically of an emeraldine salt color) is demonstrated by absorption and Raman spectroscopy, presented in Figure 3 III,IV, respectively. [ 29 ] The Raman spectra of all fi lms show, besides the typical carbon nanotubes bands (D, G, and 2D), all the bands associated to the polyaniline, emeraldine salt, confi rming the occurrence of this polymer in all samples. [ 29 ] The absorption spectra of the fi lms ( Figure 3 III) contains the three primary electronic transitions of polyaniline-emeraldine salt at approximately 350, 440, and ≈ 780 nm.…”
Section: Self-assembled Thin Films Of Carbon Nanotubes and Polyanilinementioning
confidence: 95%
“…[ 29 ] The Raman spectra of all fi lms show, besides the typical carbon nanotubes bands (D, G, and 2D), all the bands associated to the polyaniline, emeraldine salt, confi rming the occurrence of this polymer in all samples. [ 29 ] The absorption spectra of the fi lms ( Figure 3 III) contains the three primary electronic transitions of polyaniline-emeraldine salt at approximately 350, 440, and ≈ 780 nm. [ 9 , 30 ] The fi rst band is due the band gap of the polymer ( ≈ 3.2 eV), and the other two bands are assigned to polaronic/bipolaronic transitions created inside the gap by the acidic doping.…”
Section: Self-assembled Thin Films Of Carbon Nanotubes and Polyanilinementioning
confidence: 95%
“…52 The appearance of new subgap energy states and formation of quinoidal structure can be observed as changes in the UV/vis and IR/Raman spectra of polymers. 49,[52][53][54][55][56] To maintain charge balance, redox reactions associated with polymer doping are concurrent with the movement of ions into and out of the polymer matrix. 59,60 Although oxidation generally results in anion movement within the film, studies have shown that under certain conditions, cation movement occurs as well.…”
Section: Operating Principlesmentioning
confidence: 99%